PENGARUH REKRUTMEN DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT SINAR JERNIH SARANA JAKARTA SELATAN - Resti Agustini; Ahmad Syukri (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
This study aims to analyze the influence of recruitment and work discipline on employee performance at PT Sinar Jernih Sarana in South Tangerang. Recruitment is understood as the process of selecting and placing employees appropriately according to the company’s needs, while work discipline includes employee compliance with established rules and work standards. Employee performance is measured based on productivity, work quality, and efficiency in carrying out assigned tasks. This research employs a quantitative method using a survey approach and data analysis through multiple linear regression techniques. The sample consists of 100 randomly selected employees. The results indicate that effective recruitment has a positive impact on employee performance, and work discipline also significantly contributes to improving performance. Based on the analysis, it can be concluded that effective recruitment and strong work discipline can enhance employee performance at PT Sinar Jernih Sarana. Therefore, the company is encouraged to pay attention to these two factors in its efforts to improve workforce performance.